Flow injection analysis vs. ultra high performance liquid chromatography coupled with tandem mass spectrometry for determination of imatinib in human plasma - Mičová, Kateřina; Friedecký, David; Faber, Edgar; Polýnková, Adriana; Adam, Tomáš (Clinica chimica acta; international journal of clinical chemistry, 2010)
BACKGROUND: The aim of this study was to develop, validate and compare flow injection analysis (FIA) and ultra-high-performance liquid chromatography (LC)/tandem mass spectrometry methods for the determination of imatinib in plasma from patients with chronic myeloid leukemia. METHODS: The plasma for analysis by both methods was deproteinated by methanol containing d8-imatinib. The separation was achieved on a 1.7 μm C18 column with a linear gradient (4 mM ammonium formiate and acetonitrile, pH 3.2). FIA was performed at flow rate of 0.03 mL/min (0.1% formic acid in methanol). Multiple reaction monitoring mode on the tandem mass spectrometer (API 4000, AB Sciex) in positive ESI were used for detection. RESULTS: The total analysis times were 3.2 (LC) and 0.75 min (FIA). Both methods were successfully validated and applied to the plasma patients samples. The limits of quantification were 4.1 and 30.8 ng/mL; imprecisions were less than 5.7% and recovery ranged between 93 and 105%, for the LC and FIA, respectively. The methods revealed an agreement with a mean difference of 1.46 ng/mL (SD 28.95 ng/mL). CONCLUSIONS: The high-throughput methods that were developed are suitable for the therapeutic drug monitoring of imatinib in plasma. They can be used in routine clinical practice.
Keywords: Chromatography, High Pressure Liquid; Humans; Tandem Mass Spectrometry; pyrimidiny; Benzamides; imatinib mesylát; průtoková injekční analýza; Blood Chemical Analysis; Imatinib Mesylate; lidé; reprodukovatelnost výsledků; tandemová hmotnostní spektrometrie; Reproducibility of Results; chronická myeloidní leukemie; Flow Injection Analysis; piperaziny; benzamidy; biochemická analýza krve; Piperazines; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Pyrimidines; vysokoúčinná kapalinová chromatografie